1983
DOI: 10.1192/bjp.143.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol in Schizophrenia: A Double Blind, Placebo Controlled Trial of Propranolol as an Adjunct to Neuroleptic Medication

Abstract: A double blind, placebo controlled trial was carried out to examine the contribution of propranolol as an adjunct to neuroleptic medication in the treatment of chronic schizophrenic patients whose florid symptoms had not remitted with neuroleptic medication alone. Propranolol was shown to have a more beneficial effect than placebo, but the results were much less dramatic than those which have been described in previous studies. Recent work has shown that there may be a pharmacokinetic interaction between propr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 18 publications
1
17
1
1
Order By: Relevance
“…Similar negative results of the combination were reported by Myers et al [1981]. However, Pugh et al [1983] carried out a double-blind, placebo-controlled study, in neuroleptic-treated, chronic schizophrenics with florid symptoms. The duration of the study was 12 weeks and the dose of propranolol was 320 mg twice a day.…”
Section: Beta-adrenergic Receptor Blockerssupporting
confidence: 79%
“…Similar negative results of the combination were reported by Myers et al [1981]. However, Pugh et al [1983] carried out a double-blind, placebo-controlled study, in neuroleptic-treated, chronic schizophrenics with florid symptoms. The duration of the study was 12 weeks and the dose of propranolol was 320 mg twice a day.…”
Section: Beta-adrenergic Receptor Blockerssupporting
confidence: 79%
“…Does evidence exist that any adjunctive medication will reduce overt aggression or hostility in persons with schizophrenia spectrum disorders? [70][71][72]88,[132][133][134][135][136][137][138][139][140][141][142] (Table 4) Fifteen articles were identified that reported relevant data. One paper 137 was also reported in Table 5 because the subjects were preselected for aggressiveness.…”
Section: Resultsmentioning
confidence: 99%
“…In the psychiatric literature, it is recognized that placebo effect rates are low in patients with obsessive-compulsive disorder as compared with patients with other anxiety-based Axis I disorders [22]. Most studies suggest that placebo response rates in attention-deficit/ hyperactivity disorder and schizophrenia are also substantially lower than those seen in anxiety and depressive disorders [23]. The reasons for these differences are not clear.…”
Section: Placebo Responses Differ Based On Diseasementioning
confidence: 98%